How to Improve Students' Environmental Literacy on Plastic Waste Issues: Problem-Based Flipped Classroom - Maulida, Faizah; Farida, Ida; Windayani, Neneng (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
The research aimed to enhance students' comprehension of plastic waste concerns by implementing problem-based flipped classrooms, focusing on environmental literacy. Carried out on a cohort of 32 students using a one-group pre–test–post–test design, the study employed various data collection methods, including observation sheets, performance assessment rubrics, and environmental literacy assessment tools. The findings unveiled a commendable overall student engagement level, with a 95% activity rate, signifying a highly positive interpretation. Notably, students' environmental literacy exhibited advancements across knowledge, cognitive skills, and actionable behaviors. The calculated N-Gain value of 0.64 reflected substantial growth, falling within the medium interpretation range. Concerning the attitude facet, students garnered an average score of 80, with 79% expressing alignment with the prescribed attitudes, positioning them within the fairly good category. This underscores the students' positive stance toward environmental concerns. Significantly, implementing the problem-based flipped classroom model targeting plastic waste topics effectively enhanced students' environmental literacy, fostering a more comprehensive understanding of these critical issues.